From strategic planning to agility: strategic management approaches - Andrés Camilo Aponte-López; Oscar José Torrealba (Dyna)
Strategic management is fundamental to business development, but traditional strategic planning has lost its value due to uncertainty and constant market changes. Therefore, a new strategic paradigm known as agility has emerged, which promises to generate adaptation and sustainability for companies. The overall objective of this document is to examine strategic planning and organizational agility approaches, in order to understand how these paradigms can contribute to business advancement in dynamic and changing environments. A systematic review of the literature in scientific databases was carried out to achieve this. Expected outcomes include identifying differences between traditional strategic planning and organizational agility, understanding how agility can generate business adaptation and sustainability, and its implications in competitive environments. In conclusion, agility is essential for adaptation and sustainability, promoting dynamic strategies and skills such as problem solving and collaboration, improving business performance.